Peningkatan Hasil Belajar Bahasa Indonesia melalui Pendekatan Metode Inkuiri Model Kooperatif Tipe Make A Match Siswa Kelas V SD Negeri 008 Pulau Lancang - Lesta, Raja (GERAM, 2019)
The purpose of class action research carried out to improve the activities and learning outcomes of Indonesian language subject by using the Inquiry Method cooperative learning model type make a match of the fifth grade at SDN 008 Pulau Lancang, Benai District, Kuantan Singingi District. To obtain the data, researcher used observation sheet to collect student activities that were fulfilled by the observer and test the learning outcomes given at the end of the cycle. Student learning activity data was analyzed by determining the number and percentage of students involved at each meeting. The improvement of learning outcomes can be seen from the number of students who completed at the end of the cycle. The results showed that the study of learning and student learning outcomes used improvement where in the initial data from 14 students only 2 people who achieved SKM after being implemented in the first cycle increased to 8 people (57.1%) and increased in the second cycle to 85.7 students who achieve completeness, so it increased by 28.6 % but there were still some students who had not yet achieved the SKM score. Overall, it can be concluded that inquiry into the cooperative learning model type make a match can improve learning outcomes Indonesian Language of the fifth grade at SDN 008 Pulau Lancang, Benai District, Kuantan Singingi District.